2019
DOI: 10.1177/1420326x19864414
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of external shading system on cognitive task performance, alertness and visual comfort in a daylit workplace environment

Abstract: The authors examined the effect of external shading system on cognitive performance, alertness and visual comfort of visual display terminal (VDT) users under two realistic office lighting settings in this study. Daylight was the source of illumination being considered as the most significant and preferred one. A total of 26 participants performed visual and cognitive demanding tasks as well as providing subjective alertness, performance and visual evaluations in a full-scale mock-up VDT workstation. Two trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…e cause of visual problems experienced while using computers is multifactorial. While there is no strong evidence for causation [15], previous studies have reported that visual symptoms increased with the prolonged exposure to computer screens [16][17][18]. Uncorrected refractive error, presbyopia, and binocular vision abnormalities are additional factors associated with computer-related visual symptoms [6,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e cause of visual problems experienced while using computers is multifactorial. While there is no strong evidence for causation [15], previous studies have reported that visual symptoms increased with the prolonged exposure to computer screens [16][17][18]. Uncorrected refractive error, presbyopia, and binocular vision abnormalities are additional factors associated with computer-related visual symptoms [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Workplace ergonomics refers to the arrangement of equipment and furniture in an office space for users to work more efficiently and comfortably [22]. Visual or computer ergonomics on the other hand involves proper positioning of keyboard, monitor, mouse, chairs, desks, document folders, seat height, seat width and depth, seat material, backrest, materials in the office, armrests, leg room, thickness of work surface, footrest, document holder, wrist rests, and so on [15,23,24]. In a Nepalese study, users with their computer screens set below the eye level had significantly lower CVS case than those who viewed the screen at or above the eye level [25].…”
Section: Introductionmentioning
confidence: 99%
“…The features of the mock-up workstation and the furnishings are described in detail in our previous article. 38 The subjects were able to freely change their own sitting height provided that the viewing distance of 60 cm was kept in a constant position. The layout of the workstation was kept identical throughout the whole experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Table 4 shows the main values to be maintained in indoor sports halls and swimming pool, according to CONI's guidelines. (8) -24 (6) 60 ≥4 (8) -5 0.15 Changing rooms 24 (7) 70 8 0.15 Showers ≥20 (9) 60 ≥4 [73]. 2 However, since different sports present diverse requirements, International Federations often provide not only the rules regarding the game and the materials, but also standards concerning environmental parameters such as air temperature, relative humidity, and air velocity that should be maintained indoors for each sport.…”
Section: Standardsmentioning
confidence: 99%
“…The focus of researchers was often based on possible improvements of air quality [3] or on the reduction of the impact of pollutants in indoor air [4]. Visual quality and acoustical comfort have been also studied in workplaces and in educational rooms [5][6][7][8], since they may have a great impact on the focus and on the performance of the occupants. Finally, thermal comfort has been often studied in relation to the characteristic of the envelope and of the internal structures [9], as the thermal behavior of the building can largely influence the environmental conditions indoors, which also has an impact on the comfort and performance of people.…”
Section: Introductionmentioning
confidence: 99%